STUDI KADAR GIZI, SERAT DAN ANTOSIANIN TEPUNG KACANG MERAH DAN TEPUNG KECAMBAH KACANG MERAH (Phaseolus vulgaris L.) - Rizka Erwinda Sari, Ni Made; Wisaniyasa, Ni Wayan; Sri Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 3 (2020): Jurnal ITEPA, 2020)
The purpose of this study was to determine of nutrient, crude fiber and anthocyanin of red bean flour and red bean sprout flour. This study was conducted using two treatments, the first treatment without germination and the others using germination for 48 hours. Each treatment was repeated three times, then it made into flour. Red bean flour and red bean sprout flour were analyzed by paired T test. The results showed that red bean flours had a significant difference than red bean sprouts flour on water content, ash, protein, fat, carbohydrate, crude fiber, and anthocyanin. Water content, fat, carbohydrate and anthocyanin of red bean flour higher than red bean sprouts flour, but ash content, protein, and crude fiber of red bean sprouts flour higher than red bean flour. Characteristics of red bean flour and red bean sprout flour there were water content 6.33% and 5.13%, ash content 3.67% and 3.9%, fat content 4.11% and 2.81%, protein content 22.8% and 26.41%, carbohydrate content 63.09% and 61.75%, crude fiber content 3.88% and 4.17%, anthocyanin 3.37 mg/100g and 2.76 mg/100g.